An Unusual Case of Serotonin Syndrome with Oxycodone and Citalopram. (12th April 2012) - Walter, Clare; Ball, David; Duffy, Mary; Mellor, James D.
Abstract : A 77-year-old female with recurrent non-small-cell lung cancer presented to a hospital outpatient clinic with tremor, weakness, inability to coordinate motor movements, and confusion. It was suspected that the symptoms were due to possible central nervous system metastases; however, a CT scan of her head was unremarkable. The lung clinic liaison pharmacist took a medication history from the patient, complimented by extra information from the patient's community pharmacy. The pharmacist suspected the rare side effect of serotonin syndrome was responsible for the patient's presenting symptoms caused by the combination of oxycodone and citalopram. The patient's symptoms resolved soon after oxycodone was changed to morphine.